Collaborative maternity care: the relationship between independent midwives and interprofessional care providers in Johannesburg, South Africa - Du Plessis, Jeanell (My University, 2024)
This research study explored the relationships among independent midwives, obstetricians, and referral facilities in the government health care sector and how these relationships influence the quality of maternity care provided within a multi-disciplinary team. Interprofessional collaboration aims to improve communication, ensure improved, efficient, quality of patient care, provide increased access to care and assist with providing financial relief by lowering health care expenses. It is vital in maternity care environments. An exploratory, descriptive qualitative design was followed. The participants consisted of eleven independent midwives practicing in Johannesburg, two obstetricians who offer backup to independent midwives and two labour complex managers in public tertiary hospitals. Interviews were conducted with all participants. All interviews were audiotaped and transcribed verbatim. Data was analysed using thematic analysis. Study findings are discussed and supported from literature. The current relationships between the participants are described and defined. Requirements for effective collaboration that were identified in this study include trust, respect, clear role clarification and safe practices. Interprofessional collaboration is a process that was found to develop over time. Barriers to effective collaborations that were identified include ineffective knowledge of each other’s role, lack of formal policies and guidelines, reputational damage, and ineffective communication. Other barriers identified include negative attitudes and perceptions towards the independent midwives and their clients, challenges in the public sector and malpractice, unsafe and unethical behaviour. The support of management, effective communication, standardised documentation, collaborative education, and promoting mutual understanding were identified as strategies to improve collaboration. The limitations of the study were identified and recommendations for practice, nursing education and research are made.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg , 2023
Keywords: Interprofessional collaboration; Independent midwife; Maternity care providers